Prevention And Control Of Hypertension With Yoga Exercises In Sambiroto Sindon Boyolali Village - Anindita, Silviana Pusparindi; Mumtaz, Alifah Azahra Salsabila; Widyatuti, Yuli; Fitria, Cemy Nur; Sari, Anggi Luckita (Universitas Muhammadiyah Surakarta, 2024)
Hypertension is a condition of increased systolic and diastolic blood pressure that exceeds normal limits. The Silent Killer is another name for hypertension because hypertension is a disease that can be without signs and symptoms. Hypertension sufferers in the world according to WHO reach 1.28 billion adults. This disease, which can cause various complications, needs strategic efforts to overcome it. Community service by providing knowledge to the community about hypertension and yoga exercises as a form of physical activity training is an alternative chosen to increase public understanding of the dangers of hypertension and how to prevent and control it. Community service carried out in Sambiroto Sindon Boyolali village was attended by 26 local residents, both people with hypertension and those at risk of hypertension. After the community service was carried out, the level of community knowledge about hypertension increased as evidenced by the community's ability to answer the questions given. Behavior change will be realized along with the increase in the level of public knowledge so that it can reduce the high number of people with hypertension.